1991
DOI: 10.1093/infdis/163.1.187
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of an Abundant Calcium-Binding Protein in the Cytoplasm of Human Neutrophils

Abstract: Studies of experimental infections in animals indicate that phagocytic cells may sometimes control infective foci without actually ingesting or contacting the invading microorganisms. In the present study, an effective inhibitor of Candida albicans growth, previously detected in neutrophils cytoplasm and found to be released only after lysis of the cells, was identified as an abundant calcium-binding protein originally described in neutrophils as the L1 myelomonocytic antigen or the cystic fibrosis antigen. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
1
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(88 citation statements)
references
References 20 publications
3
83
1
1
Order By: Relevance
“…Currently it is not clear whether macrophages secrete ubiquicidin. The cytosolic fraction of human neutrophils also contains an antimicrobial compound, the calprotectin complex [4,5]. Based on its relative molecular mass and amino-terminal amino acid sequence, it is unlikely that ubiquicidin is the murine equivalent of one of the components of the human calprotectin complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently it is not clear whether macrophages secrete ubiquicidin. The cytosolic fraction of human neutrophils also contains an antimicrobial compound, the calprotectin complex [4,5]. Based on its relative molecular mass and amino-terminal amino acid sequence, it is unlikely that ubiquicidin is the murine equivalent of one of the components of the human calprotectin complex.…”
Section: Discussionmentioning
confidence: 99%
“…On phagocytosis of microorganisms by neutrophils, these granule-associated polypeptides are transferred to the phagolysosome where they can kill ingested microorganisms. In addition to granule-associated antimicrobial polypeptides, neutrophils also contain a cytosolic antimicrobial protein called calprotectin [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The antifungal action of this protein complex was described earlier 13,14) : calprotectin suppresses the growth of yeast and fungi. The minimum effective concentration against the growth of Candida albicans is between 10 and 20 mg/ml.…”
Section: Extracellular Function Of Calprotectinmentioning
confidence: 92%
“…Therefore, it has been reported that the concentration of calprotectin increases in extracellular fluid in various inflammatory conditions (see below), suggesting that the factor has important functions influencing the inflammatory processes. Evidence that unravels the novel functions of calprotectin is now accumulating: its extracellular functions, including antimicrobial activity, 13,14) and its regulatory activities towards cells which participate in inflammation or immunological reactions, [15][16][17][18][19] were suggested [also see reviews [20][21][22]. The exact physiological role(s) of this protein complex, however, awaits further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Together, these activities indicate a putative role in regulating leukocyte migration to inflammatory sites. S100A8/A9 is also known to inhibit microbial growth, presumably by chelating zinc (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) and to inhibit bacterial adhesion to mucosal epithelial cells (34). Thus, it is reasonable to propose a role in innate immune responses to bacterial infections for these molecules.…”
mentioning
confidence: 99%